PERAN MAJELIS ADAT ACEH DALAM PENYELESAIAN SENGKETA WARIS TERHADAP TANAH DI KECAMATAN TEMPUK TENGOH KOTA LHOKSEUMAWE - Ucha Hadi Putri (JCH (Jurnal Cendekia Hukum), 2019)
There are three inheritance legal systems in Indonesia, namely, Islamic inheritance legal system, Customary inheritance legal system and Civil inheritance legal system. The people of Aceh adhere to a parental kinship system, meaning the inheritance system in giving the position of sons and daughters, that is, equally have the opportunity to become heirs. Based on Law Number 40 of 1999 Concerning Aceh's Privileges in Article 3 paragraph 2, it is agreed that Aceh is a Special Region in the fields of adat, religion, and education. The government provides space for local communities to restore existing adat in the community, one of which is to approve the inheritance dispute that was approved by the Majelis Adat Aceh. The author is interested in conducting research on the role of the Majelis Adat Aceh in resolving inheritance disputes over land in the teungoh sub-district of Lhokseumawe, the author uses empirical juridical methods in the field at the research site with the source of the law or debate requested requested. The role of the Majelis Adat Aceh in completing the legalization has not been completed properly, from the administrative system also the application of the decision of the Majelis Adat Aceh.